2019
DOI: 10.1021/acsmacrolett.9b00518
|View full text |Cite
|
Sign up to set email alerts
|

Protein Resistance Driven by Polymer Nanoarchitecture

Abstract: We report that the nanometer-scale architecture of polymer chains plays a crucial role in its protein resistant property over surface chemistry. Protein-repellent (noncharged), few nanometer thick polymer layers were designed with homopolymer chains physisorbed on solids. We evaluated the antifouling property of the hydrophilic or hydrophobic adsorbed homopolymer chains against bovine serum albumin in water. Molecular dynamics simulations along with sum frequency generation spectroscopy data revealed the selfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…The amorphous polymer systems of interest consist of the following: PS (weight-average molecular weight ( M w ) = 30,000 g/mol, molecular weight distribution ( M w / M n ) = 1.03, Pressure Chemical Co.), P2VP ( M w = 38,500 g/mol, M w / M n = 1.01, Scientific Polymer Products, Inc.), PMMA ( M w = 35,000 g/mol, M w / M n = 1.02, Polymer Laboratories), and PB ( M w = 45,000 g/mol, M w / M n = 1.08, Sumitomo Rubber Inc.). PS and PB are hydrophobic polymers where the water contact angles were estimated to be 90 ± 1° for PS and 96° for PB, while the water contact angles of P2VP and PMMA were reported to be 67° and 73°, respectively. These polymers were chosen as rational models to determine the underlying principle of protein adsorption for two model proteins, BSA and fibrinogen, which have a higher affinity toward a hydrophobic surface compared to a hydrophilic surface …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amorphous polymer systems of interest consist of the following: PS (weight-average molecular weight ( M w ) = 30,000 g/mol, molecular weight distribution ( M w / M n ) = 1.03, Pressure Chemical Co.), P2VP ( M w = 38,500 g/mol, M w / M n = 1.01, Scientific Polymer Products, Inc.), PMMA ( M w = 35,000 g/mol, M w / M n = 1.02, Polymer Laboratories), and PB ( M w = 45,000 g/mol, M w / M n = 1.08, Sumitomo Rubber Inc.). PS and PB are hydrophobic polymers where the water contact angles were estimated to be 90 ± 1° for PS and 96° for PB, while the water contact angles of P2VP and PMMA were reported to be 67° and 73°, respectively. These polymers were chosen as rational models to determine the underlying principle of protein adsorption for two model proteins, BSA and fibrinogen, which have a higher affinity toward a hydrophobic surface compared to a hydrophilic surface …”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the inner “nematic-like” order of “trains” (adsorbed segments) and outer high-density “loops” (sequences of free segments connecting successive trains) and “tails” (nonadsorbed chain ends) of the adsorbed chains in water reduce the amount of available surfaces for the adsorbing protein, acting as a “dual” barrier against bovine serum albumin (BSA). In addition, we revealed that the formation of the nanoarchitecture in water can be generalizable across homopolymer systems with different chemical interactions, chain conformations, and chain rigidities …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The denser the water layer, the higher the energy barrier to proteins [34]. Moreover, the various nanoarchitectures of different polymers act as a dual barrier against protein adsorption [35]. Nanostructured polymeric surfaces affect the orientation and order of protein adsorption [36].…”
Section: Frictionmentioning
confidence: 99%
“…Polymers have been used in contact with dissimilar solids in a wide variety of industrial applications from traditional uses such as coating agents, adhesives and composites to innovative thin film devices, etc. [1][2][3][4][5] . The performance of the materials and devices is strongly related to the aggregation states and dynamics of polymer chains adsorbed on the solid surface [6][7][8][9][10] , which are essentially different from those in the bulk state [11][12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 99%